Digital geologic modeling applied to an iron ore open pit mine - Vieira- de-Moraes, Vandersoni Monteiro; Rodrigues-Ribeiro, Rafael; Sandoval-Salazar, Luz Dary; Hernández, Julio Alberto; Hernández-Rubiano, Nelson Olmedo; Moreno-Díaz, Jorge Oswaldo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2009)
The digital geologic modeling of diverse mineral deposits is a tool very common in all the countries where it has a highly developed mining culture. Additionally, it is a fundamental tool for deciding about the planning of investments, also to elaborate the plans of developments of a mining project. Those models are the basis of information used in reports about resources and reserves demanded by investors in mining companies listed in stock exchange market. This importance is due to the fact that the mineral resources are the main assets of a mining company. At the moment Minas Paz del Río (MPDR) is in a process of development of its procedures and has achieved a great technological advance in that area, that assured an elaboration of confident digital geologic models of their deposits. Among the contributions of those models it is possible to emphasize:a better knowledge of the time life of the deposits for a specific project; a better planning for supplying of the operation with consequent diminution of costs, and a gains in the quality of the mined ore and reduction of the variability. In this paper will be presented the methodology that was applied for theelaboration of the digital model for an open pit iron ore deposit that belongs to MPDR, where the key points for a good modeling of resources will be demonstrated, from a correct collection of initial data to the advanced geoestatistics treatments in order to have a model as close as possible to the reality of the deposit.